Acute Kidney Injury Increase Risk of Left Ventricular Remodeling: A Cohort of 1,573 Patients - Li, Qiang; Chen, Weihua; Shi, Shanshan; Huang, Haozhang; Lai, Wenguang; Liu, Liwei; Ying, Ming; Wang, Bo; Li, Huanqiang; Huang, Zhidong; Chen, Liling; Chen, Jiyan; et al. (Frontiers in Physiology, 2021)
Background: Acute kidney injury (AKI) is a common complication after coronary angiography (CAG) and associated with heart failure (HF). Left ventricular (LV) remodeling is a vital process in the progression of HF. However, few studies investigate the relationship between AKI and LV remodeling. Methods: We included consecutive patients undergoing CAG from January 2007 to December 2018 at Guangdong Provincial People’s Hospital (NCT04407936). AKI was defined as an absolute increase in serum creatinine (Scr) of ≥ 0.3mg/dl or a ≥ 50% increase in Scr from baseline within the first 48–72 h after the procedure. LV remodeling was defined as: (1) an absolute decrease in left ventricular ejection fraction (LVEF) of ≥ 10% compared to baseline, or (2) a follow-up LVEF < 40%. Univariate and multivariate logistical regressions were used to assess the association between AKI and LV remodeling. Results: Of the 1,573 patients (62.2 ± 9.7 years, female 36.7%) included in the study, 231 (14.7%) had AKI. The incidence of LV remodeling was higher in patients with AKI than in those without AKI (24.7% vs. 14.5%). After adjusting for confounding, multivariate logistic regression showed that AKI was associated with a significantly higher risk of LV remodeling [adjusted odds ratio (aOR) 1.87; 95% CI, 1.30–2.66; p < 0.001]. In addition, LV remodeling patients had higher all-cause mortality compared to non-LV remodeling patients (9.7% vs. 19.1%). Conclusion: Our data suggested that AKI is present in up to 15% of patients after CAG and that nearly a quarter of AKI patients suffered LV remodeling and AKI patients have a two-fold risk of developing LV remodeling than non-AKI patients. Our findings suggest that more active measures be taken not only to prevent AKI patient developing into LV remodeling, but to prevent patients undergoing CAG from developing AKI.